Hannah Hurst: capstone - Hurst, Hannah, artist (Colorado State University. Libraries, 2024)
The artist's statement: I am someone who prioritizes fun in my work. I get so much joy out of making art, and I seek to share a little bit of that through my pieces. Whether its bright colors or charming characters, I want my work to be entertaining for the viewer. Being a graphic designer, a lot of times this means making the work eye-catching but also legible. As someone with a deep love for illustrated books, I am fascinated by how visual imagery works together with typography. I seek to explore how illustration and typographic design overlap to effectively communicate ideas. Whether working from my own ideas or for clients, knowing when to spell things out and when to allow the imagery to speak for itself is something I like to explore in my work. In these pieces, I feel I have found a balance between clear, concise work and fun, eye-catching illustrations. I hope the audience finds enjoyment out of these pieces, just as I have in making them.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design